A categorical characterization for the compositional features of the # component model. - Heron de Carvalho Junior, Francisco (Software engineering notes.)
The # programming model attempts to address the needs of the high performance computing community for new paradigms that reconcile efficiency, portability, abstraction and generality issues on parallel programming for high-end distributed architectures. This paper provides a semantics for the compositional features of # programs, based on category theory.